Nonfarm employment and household income among ethic minorities in Vietnam - Tran, Quang Tuyen (ĐHKT, 2016)
This study examines the determinants of nonfarm participation and the effect of nonfarm employment on household income among ethnic minorities in the Northwest Mountains, Vietnam. The logistic regression analysis shows that education and the availability of local enterprises or trade villages, notably among other factors, have a significantly increasing impact on the likelihood of taking up wage employment, while the presence of paved roads gives households more chance to engage in nonfarm self-employment.